Parenting: a difficult task. (Journal of Parents and Teachers, 2014)
No one teaches us to be parents and that makes this mission one of the most complex in life. Each person educates their children as he thinks is best. But, since it can always be improved, the intention of this article is to promote a reflection on the type of parents we are and the type of educational actions that we carry out with our children.
Keywords: Educate; parents; children; difficult task; reflection.